Economic Impact Of Covid-19 Among Dental Practitioners A Cross Sectional Study - Immanuel, S.Jeswin; Balasubramaniam, Arthi (Journal of Neonatal Surgery, 2021)
Introduction: COVID-19 which meant the 21st century’s worst public health crisis. The corona virus emerged in 2019 and had a great emotional and economic impact all over the world where millions were affected. The aim of the study is to access the economic impact of COVID-19 pandemic on dental practitioners. Materials And Method: A cross sectional study was conducted employing a self administered questionnaire to the dental practitioners. A pre-validated and reliable questionnaire containing 11 questions pertaining to the economic impact of COVID-19 on dental practitioners through Google forms had been distributed to the participants. Their responses were collected and analyzed using SPSS version 23.0. Descriptive statistics and inferential statistics were performed to present the responses. Results: About 62% of participants were paid for online consultancy. A majority of dental practitioners 65.15% went on a trip/vacation. Income was increased among 63% of the dental practitioners during the pandemic. Majority (71.21%) of dental practitioners bought personal/household appliances. The difference in the economic impact during COVID-19 among the male and female participants was found statistically not significant (p>0.05). Conclusion: Most of the dental practitioners have not faced an economic crisis during the COVID -19 pandemic. In fact their income had increased during the lockdown due to shutdown of many dental clinics in rural areas.